2016
DOI: 10.1128/mbio.00331-16
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Underlying the Delayed Activation of the Cap1 Transcription Factor in Candida albicans following Combinatorial Oxidative and Cationic Stress Important for Phagocytic Potency

Abstract: Following phagocytosis, microbes are exposed to an array of antimicrobial weapons that include reactive oxygen species (ROS) and cationic fluxes. This is significant as combinations of oxidative and cationic stresses are much more potent than the corresponding single stresses, triggering the synergistic killing of the fungal pathogen Candida albicans by “stress pathway interference.” Previously we demonstrated that combinatorial oxidative plus cationic stress triggers a dramatic increase in intracellular ROS l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 55 publications
0
27
0
1
Order By: Relevance
“…Multiple individual imposed toxic stresses have been shown to exert synergistic effects on the ability to kill Candida . These studies illustrate the importance of the Hog1 MAPK and the Cap1 transcription factor in the regulation of combinatorial stress responses [ 60 , 61 ].…”
Section: Resisting Phagocytesmentioning
confidence: 95%
“…Multiple individual imposed toxic stresses have been shown to exert synergistic effects on the ability to kill Candida . These studies illustrate the importance of the Hog1 MAPK and the Cap1 transcription factor in the regulation of combinatorial stress responses [ 60 , 61 ].…”
Section: Resisting Phagocytesmentioning
confidence: 95%
“…In particular, host defence mechanisms are perceived as stresses by the pathogen. Myeloid cells attempt to kill fungal cells using a range of toxic reactive oxygen and nitrogen species 9 , and it was recently shown that a combination of cationic (NaCl) and oxidative stresses are particularly lethal for pathogenic Candida species 10 , 11 . Therefore, an understanding of stress response mechanisms could potentially lead to therapeutic approaches that augment host defence.…”
Section: Introductionmentioning
confidence: 99%
“…Strikingly, studies investigating the mechanistic basis underlying the exquisite sensitivity of C. albicans to such combinations of stress have revealed that exposure to cationic stress prevents this pathogen from mounting an oxidative stress response. The oxidative stress regulon in C. albicans is largely regulated by the Cap1 AP-1-like transcription factor (214), and Cap1 fails to be activated following exposure to combinatorial oxidative and cationic stress (211, 215). This phenomenon, which has been termed “ stress pathway interference ” (211) (Figure 3), contrasts starkly with that of stress cross-protection in which exposure to one stress protects against the subsequent exposure to a different stress (104).…”
Section: Adapting To Stress In Natural Environmentsmentioning
confidence: 99%
“…First, cations inhibit catalase activity which triggers significant increases in intracellular ROS levels following combinations of cationic and oxidative stresses (211). Such high levels of ROS trap Cap1 in a partially oxidised form that fails to induce target antioxidant-encoding genes (215). Second, cations stimulate the interaction of Cap1 with the nuclear export factor Crm1, which results in significant delays in the H 2 O 2 -induced nuclear accumulation of this transcription factor.…”
Section: Adapting To Stress In Natural Environmentsmentioning
confidence: 99%